1999
DOI: 10.1038/sj.onc.1202314
|View full text |Cite
|
Sign up to set email alerts
|

Mutant p53 gain of function: differential effects of different p53 mutants on resistance of cultured cells to chemotherapy

Abstract: Many tumors overexpress mutant forms of p53. A growing number of studies suggest that the nature of a p53 mutation in a cell can impact upon cellular properties, clinical responses to therapy and prognosis of a tumor. To explore the cellular basis of these observations, experiments were designed to compare the properties of cells with and without p53 mutations within the same cell population. To that end, various tumorderived human p53 mutants were introduced into p53-null H1299 lung adenocarcinoma cells. Clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
348
1
5

Year Published

1999
1999
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(362 citation statements)
references
References 37 publications
8
348
1
5
Order By: Relevance
“…Thus, mutant p53 can regulate gene expression independently of wt p53 (Kim and Deppert 2004), and transfection of mutant p53 into p53-null cell lines enhances their tumorigenic potential (Dittmer et al, 1993) and renders them resistant to apoptosis (Li et al, 1998;Blandino et al, 1999;Matas et al, 2001). In keeping with these observations, p53-mutant transgenic mice are more prone to cancer than p53 knockout mice (Harvey et al, 1995;Liu et al, 2000).…”
Section: Introductionmentioning
confidence: 84%
“…Thus, mutant p53 can regulate gene expression independently of wt p53 (Kim and Deppert 2004), and transfection of mutant p53 into p53-null cell lines enhances their tumorigenic potential (Dittmer et al, 1993) and renders them resistant to apoptosis (Li et al, 1998;Blandino et al, 1999;Matas et al, 2001). In keeping with these observations, p53-mutant transgenic mice are more prone to cancer than p53 knockout mice (Harvey et al, 1995;Liu et al, 2000).…”
Section: Introductionmentioning
confidence: 84%
“…Particular attention was devoted to the ability of mutp53 to impinge upon apoptotic pathways, primarily as this might be important in the context of efficient killing of tumor cells by chemotherapy and radiotherapy. Here, mutp53 gain of oncogenic function was manifested as the ability of various p53 mutants to interfere with apoptotic cell death upon treatment with various stress inducers, including growth factor deprivation and genotoxic agents such as IR, UV radiation, cisplatin, etoposide, doxorubicin, and a-amanitin (Peled et al, 1996;Li et al, 1998;Blandino et al, 1999;Murphy et al, 2000;Matas et al, 2001;Sigal et al, 2001;Yap et al, 2004). Mutp53 was also reported to protect hepatocytes from a combination of HBV-X protein and TNFa (Lee et al, 2000).…”
Section: Oncogenic Activities Of Mutp53mentioning
confidence: 99%
“…The attempt to verify whether the structural classification of p53 mutants reveals similar differences in terms of biological activities has been quite difficult to tackle. In vitro studies have shown that the overexpression of conformational p53 mutants renders cell cultures more resistant to etoposide, whereas DNA defective mutants increases the resistance to cisplatin (Gualberto et al, 1998;Li et al, 1998;Blandino et al, 1999;Sigal and Rotter, 2000). The presence of conformational mutants has been associated with breast cancer patients, whose relapse after conventional chemotherapy occurred more frequently when compared with patients carrying DNA contact defective p53 mutants (Aas et al, 1996;Berns et al, 2000;Geisler et al, 2003).…”
Section: Introductionmentioning
confidence: 99%